Log in to add a comment

## Answers

### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Here is a simple way of solving it

We let:

2x + y = 9 ... [1]

2x - y = 11 ... [2]

[1]-[2]

2x + y =9

y=-1

We just substitute this to one of the equations:

2x-1=9

2x=10

x=5

You can actually just do [1]+[2]

2x +y =9

We let:

2x + y = 9 ... [1]

2x - y = 11 ... [2]

[1]-[2]

2x + y =9

__-2x -(-y) = -11__

2y=-2y=-1

We just substitute this to one of the equations:

2x-1=9

2x=10

x=5

You can actually just do [1]+[2]

2x +y =9

__+2x -y =11__

4x =20____ x=5### This Is a Certified Answer

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

2x+y=9

2x-y=11

Using elimination method, remove y

4x=20

Divide both sides by 4

x=5

Now to solve y, just substitute the value of x to any equation

2x+y=9

2(5)+y=9

10+y=9

Subtract both sides by 10

y=-1

Hope this helps =)

2x-y=11

Using elimination method, remove y

4x=20

Divide both sides by 4

x=5

Now to solve y, just substitute the value of x to any equation

2x+y=9

2(5)+y=9

10+y=9

Subtract both sides by 10

y=-1

Hope this helps =)